2015
DOI: 10.1161/atvbaha.115.305806
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Promotes Collateral Artery Growth Mediated by Monocytic Nitric Oxide

Abstract: Objective-Collateral artery growth (arteriogenesis) is an important adaptive response to hampered arterial perfusion.It is unknown whether preventive physical exercise before limb ischemia can improve arteriogenesis and modulate mononuclear cell function. This study aimed at investigating the effects of endurance exercise before arterial occlusion on MNC function and collateral artery growth. Approach and Results-After 3 weeks of voluntary treadmill exercise, ligation of the right femoral artery was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Replenishing these potentially reparative CD14 + CD16 ++ monocytes might provide a novel therapeutic option. Evidence that mononuclear cell transfer can mediate exercise-induced collateral artery growth in mice illustrates monocyte transfer as an amenable therapeutic approach21.…”
Section: Discussionmentioning
confidence: 99%
“…Replenishing these potentially reparative CD14 + CD16 ++ monocytes might provide a novel therapeutic option. Evidence that mononuclear cell transfer can mediate exercise-induced collateral artery growth in mice illustrates monocyte transfer as an amenable therapeutic approach21.…”
Section: Discussionmentioning
confidence: 99%
“…Together with neuronal NOS (nNOS), eNOS is constitutively expressed. On the other hand, a third form of NOS, inducible NOS (iNOS), is produced in response to insults in monocytes/macrophages, but also in MNCs with angiogenic activity, with recent evidences pointing to a potential role of iNOS in the control of angiogenesis (27)(28)(29).…”
Section: The Enos Signaling Pathway and The Control Of Angiogenesismentioning
confidence: 99%
“…89,90 Additional research has shown that excess NO, often due to inducible NOS (iNOS) leads to loss of endothelial integrity in diseases like atherosclerosis, 91 despite the fact that exercise was shown to promote healthy arteriogenesis in an iNOS-dependent manner. 92 …”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%